Encouraging class discussion and promoting learning performance through Facebook / Norasyikin Abdul Malik and Puteri Rohani Megat Abdul Rahim - Abdul Malik, Norasyikin; Megat Abdul Rahim, Puteri Rohani (Akademi Pengajian Bahasa, 2019)
English language is undeniably significant in this globalization era. Thus, there is an urgent need among the second language educators to find ways to assist L2 learners in using the target language. However, research has shown that majority of L2 learners are not confident in using the language. As a result, they seldom take part and are passive during class discussion. The aim of this study is to find an avenue to promote student's self-confidence in using the language and directly lessen the language apprehension that makes them to be passive in classroom. This study focuses on the use of Facebook to boost L2 learners' confidence to participate in class discussion. Three classes of diploma students were randomly selected for this study. Data from observation, pre-test and post-test were employed for this study. Observation of students' participation and discussion in the Facebook groups and also classroom setting was conducted. The students were assigned reading materials via Facebook and were requested to interpret and share their thoughts of the text in the medium provided apart from the usual discussion in classroom context. The findings showed that both intervention groups showed positive involvement in class discussion both via cyberspace and classroom context. The respondents in the control groups did not show significant changes of behaviour in classroom con- text. However, for the intervention groups despite receiving the same stimulus the students in the two intervention groups responded differently through this medium. The findings illustrated there were regression in the post-test during the first intervention, while in the second intervention group there was a positive growth in the post-test where 71% respondents recorded a change in the attitude during the process of learning. The result showed that there are other factors to consider when employing Facebook as a tool to interact. Nevertheless, the study brings to light the prospective of using Facebook in building students' confidence in expressing thoughts and consequently improves their performance.